Comparison of Puncture Outcome between Needle versus Cannula over needle Technique for Radial Artery Cannulation during Distal Transradial Coronary Interventions - Shadly, Tausif Amim; Uddin, Mir Jamal; Momen, Abdul; Shahriar, Saqif; Hasan, Md. Zahid; Ghose, Sujan; Mondal, Kanak Jyoti; Chowdhury, Md. Faizul Hafiz; Kabir, Md. Khairul; Bhowmik, Goutom Chandra; Hosen, Imam (Cardiology and Cardiovascular Medicine, 2025)
Background: Radial artery access by distal transradial approach (dTRA) is obtained using either Needle technique or Cannula over Needle technique. In Needle technique only anterior wall of radial artery is punctured (modified seldinger technique), whereas, both anterior and posterior wall are punctured with Cannula over needle (Seldinger technique). There is no previous comparative evaluation of the safety and feasibility of these two techniques in dTRA. Methods: One hundred twenty patients undergoing distal transradial catheterization were randomized to group I (n=60) Needle technique, and group II (n=60) Cannula over needle technique. Demographic and procedural data were collected at the time of the procedure. Patient was observed for any complication after procedure and a duplex USG of radial artery done at 24hr after procedure to detect RAO. Results: Age, gender, weight, height, history of diabetes mellitus, hypertension, dyslipidemia and smoking were comparable between groups I and II. Access time (4.7 ± 2.1 vs 4.3 ± 2.1 min, p=0.046), number of attempts to get access (1.75 ± 0.8 vs 1.45 ± 0.68, p=0.025), were significantly different favoring group II. Access was obtained at first attempt in 45% of patients in group I compared with 65% in group II (P < 0.001). Change in access site (crossover) was required in 10% of group II patients, compared with 20% crossover in group I (P < 0.0001). Incidence of hematoma (10% vs. 6.7%, P > 0.2), RAS (11.7% vs 8.3%, P>0.5) and RAO (10% vs 5%, P > 0.4) was comparable between groups I and II and not statistically significant. Conclusion: Cannula over needle technique was superior than Needle technique in term of efficacy but complication rate was comparable in dTRA.